CCNP ROUTE portable command guide - Empson, Scott; Roth, Hans, 1953- (Indianapolis, IN : Cisco Press, 2010)
The guide summarizes all CCNP certification-level Cisco IOS Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real -world scenarios.
rua 30/10/13
Loans
Keywords: Routers (Computer networks) -- Examinations -- Study guides; Routing protocols (Computer network protocols) -- Examinations -- Study guides; Internetworking (Telecommunication) -- Examinations -- Study guides; Telecommunications engineers -- Certification -- Examinations -- Study guides